Pharmacokinetics and bioequivalence testing of generic ondansetron preparations in healthy Thai male volunteers - Rojanasthien N. (2014)
Pharmacokinetics and bioequivalence of oral preparations of generic ondansetron were investigated in healthy Thai males. The test preparations were Vomitron 8 and Vomitron 4, the reference was Zofran. The three products were administered as an 8 mg single oral dose, in a three-period four-sequence cross-over design with one-week washout period. An intravenous 8 mg Zofran was administered on the forth visit. Plasma ondansetron concentrations were determined by HPLC and the pharmacokinetic parameters were analyzed by non-compartmental analysis.